Influence of COVID-19 pandemic on the distribution and drug resistance of pathogens in patients with bloodstream infection - Liu, Yuanyuan; Song, Hui; Wu, Yanli; Liu, Lihua; Li, Ning; Zhang, Min; Li, Yusen; Meng, Xiujuan (Frontiers in Public Health, 2025)
BackgroundThe pandemic of Coronavirus Disease 2019 (COVID-19) significantly impacted healthcare systems worldwide, especially improving awareness of infection prevention and control in medical institutions. However, it remains unclear to what extent COVID-19 influenced the occurrence of bloodstream infection (BSI). This study aimed to analyze the distribution and antibiotic resistance patterns of pathogens responsible for BSI before and after the COVID-19 pandemic in a tertiary hospital.MethodsPathogens from patients with BSI were collected from January 2018 to December 2022. Pathogen identification was performed using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). Antimicrobial susceptibility testing was conducted using broth microdilution, the Kirby-Bauer (K-B) disk diffusion method, and Etest. Data were analyzed using WHONET and SPSS software. This study was approved by the Medical Ethics Research Committee of the hospital (2023-11-C026).ResultsFollowing the COVID-19 pandemic, the blood culture submission rate decreased from 12.82 to 11.07%, while the standardized blood culture positivity rate increased from 0.53 to 0.62%. Among the identified pathogens, Gram-negative bacteria accounted for 67.90%, Gram-positive bacteria for 28.82%, and fungi for 3.28%. The most frequently isolated pathogens were Escherichia coli, Klebsiella pneumoniae, and Staphylococcus aureus. The resistance rate of E.coli to ciprofloxacin increased from 60.10 to 66.84% post-pandemic, whereas K. pneumoniae showed a reduction in cefepime resistance, decreasing from 25.42 to 15.54%. Additionally, the proportion of extended-spectrum beta-lactamase (ESBL)-producing E. coli increased from 35.93 to 50.63%. In contrast, S. aureus exhibited no significant changes in resistance to commonly used antibiotics post-pandemic.ConclusionThe COVID-19 pandemic impacted the distribution and antibiotic resistance of pathogens in patients with BSI. Notably, the prevalence of ESBL-producing E. coli were increased, while the isolation rates of other multidrug-resistant organisms remained relatively stable.